The RESPONS KEBIJAKAN INDONESIA TERHADAP PERUBAHAN IKLIM: STUDI LITERATUR TENTANG MITIGASI, ADAPTASI, DAN TANTANGAN IMPLEMENTASI - Bulan Erika Bato; Santi Rande; Lara Ayu Lestari; Dyah Rahayu Perwitasari; Iqbal Saputra Zana (Polteknik Ilmu Pemasyarakatan, 2025)
Indonesia, as an archipelagic country, is highly vulnerable to climate change, experiencing sea-level rise, intensified floods and droughts, and altered rainfall patterns affecting food security, coastal areas, and natural resources. In response, the government has outlined mitigation and adaptation strategies, including commitments under the Paris Agreement through the Nationally Determined Contributions (NDCs), aiming for a 29% emissions reduction by 2030, with up to 41% achievable with international support. Local initiatives such as the Climate Village Program (ProKlim) focus on community-based adaptation, while renewable energy is targeted to constitute 23% of the national energy mix by 2025. This qualitative study, based on a literature review of policy documents, international reports, and scientific articles, uses content analysis to explore climate change mitigation, adaptation, financing, and implementation challenges in Indonesia. The findings highlight key policies like RAN-GRK, RAN-API, and ProKlim, with mitigation efforts focused on deforestation, ecosystem restoration, and clean energy. Adaptation strategies center on community empowerment and local resource management. However, challenges remain, including weak coordination, law enforcement, limited private sector engagement, and inadequate domestic financing. Recommendations include improving coordination, enhancing green investment incentives, optimizing financing, and strengthening regulatory enforcement. This study aims to inform more effective and sustainable climate change policies in Indonesia.